PEMETAAN KLASTER KERAJINAN SEBAGAI LANGKAH PEMBENTUKAN RUTE KUNJUNGAN WISATA KERAJINAN DI JEPARA - Indrahti, Sri; Laksono, Arido (HUMANIKA, 2014)
The development of handicraft tourism in the regency of Jepara attempts to empower local communities as the owners and preservers of local values. Several clusters that become the focus of the study in this research involve the clusters of furniture and woodcarving, sculpture, rattan, troso weaving, batik painting and monel. Some clusters are not ready yet to welcome the idea of handicrafts tourism. However, the clusters of furniture and woodcarving, troso weaving and sculpture have claimed to be ready for the establishment of handicrafts tourism. Some of the factors that strengthen the readiness of the three mentioned clusters are the establishment of a local community that is able to accommodate business networks and the readiness of local artisans and entrepreneurs in providing tourist services as part of economic activities.Â  It apparently requires a long process of socialization, nevertheless, the local culture as the communityâ€™s potential is expected to encourage the readiness of the community.